Analisis Faktor Minat Membaca Siswa Kelas 4 Melalui Pendekatan Pembelajaran Kooperatif: Analysis of Reading Interest Factors of Grade 4 Students Through a Cooperative Learning Approach - Alif Haqque; Sri Bintang; Harumi Siregar (ITScience (Information Technology and Science), 2025)
This study aims to analyse the factors that influence the reading interest of fourth-grade students through a cooperative learning approach. The background of this study is based on the low reading ability of students, most of whom are still at the stage of recognising letters and spelling, even though they should have reached the reading stage with comprehension. The research method used in this article is a descriptive qualitative approach implemented at Ar-Ridha Marelan Islamic Private Elementary School, Medan City, North Sumatra. The study population consisted of all 60 fourth-grade students, with a purposive sampling technique used to select 3–5 students representing various levels of reading interest, namely high, medium, and low. Research data were obtained through observation, semi-structured interviews, and documentation of students selected purposively.In contrast, data analysis was carried out using an interactive analysis model consisting of data collection, reduction, presentation, and conclusion drawing. This process is simultaneous and iterative. The study results indicate that students' reading interest is shaped by the interaction between internal factors, such as motivation, habits, and individual needs, and external factors, such as family, teacher, and peer support. Cooperative learning has been proven effective in increasing reading interest by creating a collaborative learning environment, encouraging active student engagement, and strengthening social interactions that support literacy development. This study recommends a cooperative learning approach to improve elementary school students' reading interest and skills sustainably.